Association of Salt-Reduction Knowledge and Behaviors and Salt Intake in Chinese Population - Bing Han; Chuancang Li; Yabing Zhou; Mengge Zhang; Yang Zhao; Ting Zhao; Dongsheng Hu; Liang Sun (Frontiers Media S.A., 2022)
ObjectiveExcessive salt intake is causally associated with an increased risk of cardiovascular disease. Salt-reduction strategies have been rapidly deployed across China since 2017. This study aimed to investigate the association of salt-reduction knowledge and behaviors and salt intake in Chinese population.Study DesignThis study was a national cross-sectional study in China.MethodsThis cross-sectional study was based on data collected during a Chinese adult chronic disease and nutrition surveillance program in 2018 with 7,665 study participants. Salt intake was assessed by calculating 24 h urine sodium from morning urine samples. Logistic regression and mean impact value (MIV) based on the back propagation (BP) artificial neural network were used to screen the potential influencing factors.ResultsA total of 7,665 participants were included in the analysis, with an average age of 54.64 ± 13.26 years, and with men accounting for 42.6%. Only 19.3% of the participants were aware of the Chinese Dietary Guidelines, and only 7.3% of them could accurately identify the level of salt intake recommended in the Chinese Dietary Guidelines. Approximately 41% of the participants adopted salt-reduction behaviors, among whom the number of participants who used less salt when cooking was the highest, and the number of participants who used low sodium salt was the lowest. In the logistic regression, only "No extra salt was added at the table" group showed the effect of salt-reduction, the odds ratio (OR) being 0.78 (95% confidence interval [CI]: 0.64-0.95). The MIV result based on the BP neural network showed that the most important salt-reduction behavior was using less salt when cooking, while reducing eating-out behavior and using salt-limiting tools were the least important.ConclusionThe research shows that the popularization of salt-reduction knowledge and behaviors can reduce the population's salt intake. However, there is still considerable scope for promoting salt-reduction knowledge and behaviors, while the promotion of salt-reduction tools and low-sodium salt still needs to be strengthened.